2016
DOI: 10.4103/2230-8210.192921
|View full text |Cite
|
Sign up to set email alerts
|

Fasting practices in Tamil Nadu and their importance for patients with diabetes

Abstract: Religious practices and cultural customs related to eating habits have a significant impact on lifestyle and health of the community. The Ramadan fasting in Muslims and its influence on various metabolic parameters such as diabetes have been reasonably studied. However, literature related to Hindu religious customs related to fasting and food patterns during various festivals and its effect on diabetes are scarce. This article is an attempt to describe the Hindu religious customs related to fasting and food pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…With careful planning and education, patients may be able to participate in the number of feasts and fasts that dot the Indian calendar with the same vigor and zest. 10 In the current study many participants reported dependency on family either economically or physically. But some of them were not getting the required support.…”
Section: Discussionmentioning
confidence: 65%
“…With careful planning and education, patients may be able to participate in the number of feasts and fasts that dot the Indian calendar with the same vigor and zest. 10 In the current study many participants reported dependency on family either economically or physically. But some of them were not getting the required support.…”
Section: Discussionmentioning
confidence: 65%
“…During the breaking fast, meal usually consists of rice, greens ("agathi keerai"), gooseberry (amla) and turkey berry (sundaikai) [95]. Yom Kippur fasting: like prolonged fasting (PF), it is observed by Jews for 25 h to celebrate the tenth day of the seventh month of the Hebrew calendar.…”
Section: Types Of Religious Fastingmentioning
confidence: 99%
“…In an "uppuma"like preparation made out of rice and jaggery and a gravy with lentils, seven or nine seasonal vegetables are offered to God during the dawn of the day and eaten. [9] Today, there are many articles on fasting and autophagy. Fasting is the most effective way for the trusted source to trigger autophagy.…”
Section: Decembermentioning
confidence: 99%